A positive plate for high-rate, long-cycle, high-safety lithium battery and a preparation method and application thereof
Patent Information
- Application Number
- CN202210113785.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-30
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2042-01-30
AI Technical Summary
缺点:方法工艺复杂,影响电池倍率性能
本发明的锂电池正极表面功能层中的组分1或组分1与组分2的混合组分颗粒化学稳定性高,可以在正极片制备后通过表面涂覆方式加入到正极当中,不改变当前正极片、隔膜和电池的主流制备工艺,与现有锂离子电池正极片的主流制备工艺相兼容,不影响正极和电芯的制备工艺,具有稳定性高、成本低的优势,适合大规模应用。相比之下,正极材料掺杂或正极表面包覆的方法都需要改变现有正极材料制备技术,难以同时提高放电比容量和倍率性能。
Smart Images

Figure CN116565141B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery technology, and in particular to a positive electrode sheet for high-rate, long-cycle, and high-safety lithium batteries, its preparation method, and its application. Background Technology
[0002] Lithium-ion batteries have advantages such as high energy density, good cycle performance, long service life, low self-discharge, and no memory effect. They are gradually occupying a larger application market in energy storage, power batteries, and 3C electronics, and have broad application prospects.
[0003] Lithium-ion batteries are continuously being developed towards higher energy density to provide better range for electric vehicles, digital products, and other power electronic devices. Increasing the loading and compaction density of electrode plates, especially the positive electrode plate, is an effective way to improve battery energy density. However, as the loading and compaction density of the positive electrode plate increase, the active material layer thickens and the porosity decreases, making lithium-ion transport within the positive electrode plate difficult. This leads to severe battery polarization, a decrease in the battery's discharge specific capacity and rate performance, and a reduction in cycle stability. Simultaneously, as battery energy density increases, battery safety often becomes more difficult to guarantee. To date, no technology can simultaneously solve all of these problems.
[0004] Existing methods for improving battery rate performance include: Cathode surface doping: Patent application CN113224287A discloses a strontium-doped ternary lithium-ion battery cathode material (Li). 1-x Sr x [Ni 1-y-z Co y M z [O2, where M is one of metals Mn and Al, 0 < x ≤ 0.1, 0 < y ≤ 1, 0 < z ≤ 1) and its preparation method and applications. By doping lithium sites with strontium metal ions, the degree of cation mixing is reduced, lithium ion channels are expanded, and the layered structure is stabilized, effectively improving the rate performance of lithium batteries. However, while this method improves rate performance, it often leads to accelerated capacity decay.
[0005] Existing methods for improving battery safety performance include: Cathode Coating: Patent application CN113809280A discloses a cathode material and its preparation and application. By modifying the sintering technique and utilizing the interaction between the coating agent, a cathode material with a near-planar coating effect is prepared. The cathode material prepared by this method has a large surface coating coverage, significantly reducing the erosion of material particles by the electrolyte, effectively reducing the probability of side reactions, and thus improving material safety. Disadvantages: The method is complex and affects battery rate performance.
[0006] Electrolyte additives: Patent application CN113690490A discloses a phosphite-based lithium-ion battery electrolyte additive that effectively prevents the combustion or explosion of organic solvents, improves the thermal stability of the electrolyte itself, enhances the stability of the positive electrode, and improves the stability and safety of battery cycle performance. Disadvantages: It can impair battery electrical performance, such as cycle performance and rate performance.
[0007] Separator Coating: Patent application CN108963153B discloses a lithium-ion battery separator and its preparation method. This method involves coating at least one side of a base film layer with an aqueous ceramic slurry coating, followed by coating the aqueous ceramic slurry coating and / or the base film layer with a composite adhesive layer made of polyethylene glycol and polymethyl methacrylate. The resulting lithium-ion battery separator exhibits excellent adhesion properties, preventing short circuits due to electrode misalignment, and improving battery hardness, thereby significantly enhancing battery safety. Disadvantage: It impairs battery rate performance.
[0008] Existing methods for simultaneously improving battery electrical performance and safety performance: CN 108365260 B discloses a quasi-solid-state electrolyte, the raw material composition of which includes a polymer, a ceramic electrolyte, a lithium salt, and an ionic liquid. The ceramic electrolyte comprises a main phase of lithium aluminum titanium phosphate and a heterogeneous phase of TiP2O7 / TiO2. Preferably, the heterogeneous phase content in the ceramic electrolyte is 2-7%, and the mass ratio of TiP2O7 to TiO2 is 1.5-2.5:1. The quasi-solid-state electrolyte prepared from the ceramic electrolyte with this heterogeneous phase content exhibits the best overall performance. The heterogeneous phase with this specific composition and content possesses lithium storage characteristics, which can improve lithium-ion transport performance and reduce the contact between the main phase of lithium aluminum titanium phosphate and metallic lithium, thereby improving the interfacial stability with metallic lithium. However, this patent does not improve the positive electrode's electrical performance and safety performance, and the method is incompatible with the mainstream preparation process of existing lithium-ion battery positive electrodes, making it unsuitable for large-scale applications.
[0009] CN113707880A relates to a positive electrode containing a solid electrolyte, its preparation method, and its application, aiming to improve the rate performance, cycle performance, and safety performance of batteries. Because the solid electrolyte in the positive electrode slurry facilitates the transverse and longitudinal transport and wetting of the electrolyte on the electrode, it is beneficial for electrolyte storage and wetting. During cell cycling, it also helps to alleviate electrode expansion and reduce the amount of electrolyte squeezed out under pressure, ensuring that the electrode still contains sufficient electrolyte after long-term cycling, guaranteeing normal lithium-ion transport and thus improving cycle performance. However, based on the data from the embodiments, battery capacity and safety are only slightly improved, and there is a lack of data to support the effect on rate performance. This indicates that adding conventional solid electrolytes cannot achieve the goal of comprehensively improving battery electrical and safety performance.
[0010] Therefore, there is still a need to find a simple and cost-effective method that can improve both battery performance and safety. Summary of the Invention
[0011] To address the limitations of the existing technology, this invention provides a high-rate, long-cycle, high-safety positive electrode sheet for lithium batteries, its preparation method, and its application. The positive electrode sheet of this invention includes a positive electrode material layer and a functional layer directly located on the positive electrode material layer.
[0012] The functional layer material includes component 1, which is selected from Li 1-x1 Ti 1-x1 A x1 OPO4, Li 1-x1 Ti 1-x1 A x1 PO5, Li 2- y1 Ti 1-y1 A y1 OM1O4, Li 2-y1 Ti 1-y1 A y1 At least one of M1O5. Wherein 0≤x1≤0.7, 0≤y1≤1, A is selected from at least one of Nb, Ta, and Sb, and M1 is selected from at least one of Si and Ge; Component 1 is preferably LiTiOPO4, Li 0.9 Nb 0.1 Ti 0.9 OPO4, Li 0.9 Ta 0.1 Ti 0.9 At least one of OPO4, Li2TiOSiO4, and LiTaOGeO4.
[0013] The functional layer material further includes component 2, which is selected from LiM22(PO4)3, Li 1+x2Al x2 M2 2-x2 (PO4)3, M2O2, Li 16-4y2 M2 y2 O8, M2P2O7, M3PO4, M32SiO5, M43(PO4)2, at least one or a combination of more than one of M42SiO4, wherein M2 is selected from one of Ti, Ge, Zr and Hf, 0 < x2 < 0.6, M3 and M4 are each one of Al, Ga, Sc, Y, Ca, Sr, Zn, Si, In, Lu, La, Fe, Cr, Ge, and 3 < y2 < 4; the component 2 is preferably one of InPO4, LATP, AlPO4, LAGP, LATP+AlPO4, LAGP+Al2SiO5, InPO4+LATP, Al2SiO5TiO2+LiTi2(PO4)3, TiP2O7+LiGe2(PO4)3.
[0014] The form of the mixed component composed of component 1 and component 2 in the functional layer may be a uniform mixture between component 1 particles and component 2 particles, or each primary particle may contain both the crystal form of component 1 and the crystal form of component 2.
[0015] The functional layer is of a porous structure, with a porosity p, where 20% ≤ p ≤ 80%, and a thickness h, where 0 μm < h ≤ 10 μm.
[0016] The particle size of the component 1 is 10 nm to 10 μm. Preferably, the particle size of the component 1 is 50 nm to 1 μm.
[0017] The particle size of the component 2 is 10 nm to 10 μm. Preferably, the particle size of the component 2 is 50 nm to 1 μm.
[0018] Preferably, the positive active material particles are selected from at least one of lithium cobalt oxide positive electrode and its modified materials, NCM ternary positive electrode and its modified materials, NCA ternary positive electrode and its modified materials, lithium nickel manganese oxide positive electrode and its modified materials, lithium-rich positive electrode and its modified materials, and lithium iron phosphate positive electrode and its modified materials; The conductive agent is selected from at least one of Super-P, KS-6, carbon black, carbon nanofibers, carbon nanotubes, acetylene black or graphene; The binder is selected from polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polytetrafluoroethylene, homopolymers, copolymers, modified compounds of the above polymers, or mixtures of the above polymers with other polymers or small molecules.
[0019] A second objective of this invention is to provide a method for preparing a positive electrode sheet for lithium batteries, as described in one of the objectives of this invention. Component 1 or a mixture of component 1 and component 2 is formed as a functional layer on the surface of the positive electrode material layer by coating the positive electrode surface. The slurry comprising component 1 or a mixture of component 1 and component 2 is coated onto the surface of the positive electrode sheet. Because the electrode sheet has a porous structure, the coating process allows some particles of component 1 or the mixture of component 1 and component 2 to penetrate and disperse between the positive electrode active material particles, in addition to forming a coating on the positive electrode surface.
[0020] Preferably, the preparation method includes the following steps: Step 1: Prepare the positive electrode active layer; Step 2: Mix component 1 or a mixture of component 1 and component 2 with the solvent until homogeneous, and grind into a slurry of 10nm-10um. Step 3: Add binder to the slurry obtained in Step 2 and mix evenly to prepare a coating slurry; Step 4: Coat the slurry obtained in Step 3 onto the positive electrode active layer and dry it to obtain the positive electrode sheet.
[0021] Preferably, In step two, The solvent used in the slurry is at least one selected from deionized water, ethanol, NMP, alcohol, isopropanol, and acetone. The mass ratio of the solvent to the cathode material is (2000-10):100.
[0022] In step four, The temperature of the blower drying is 80-180℃, and the time is 10 minutes to 9 hours; the temperature of the vacuum drying is 80-180℃, and the time is 3-100 hours.
[0023] A third objective of this invention is to provide the application of the positive electrode sheet described in one objective of this invention in lithium batteries.
[0024] The lithium battery is either a liquid battery or a solid battery.
[0025] This invention coats a functional layer onto the surface of the positive electrode using a surface coating method. The functional layer contains component 1 or a mixture of component 1 and component 2 with a particle size D50 of 0.01-10 µm, improving the rate performance, cycle performance, and safety performance of the battery. In the prior art, component 1 is generally considered to be an impurity phase that appears during the solid electrolyte sintering process. The presence of such impurities reduces the ionic conductivity of the solid electrolyte and therefore needs to be removed during solid electrolyte preparation. In other words, it is generally believed that this type of component cannot be used in solid electrolytes due to its extremely low ionic conductivity. However, through extensive experiments, we have found that although this type of component has a low ionic conductivity, it is far lower than the ionic conductivity of common solid electrolytes by approximately 10 µm.-4 S / cm, which is even smaller than the ionic conductivity of the electrolyte by about 10. -2 While component 1, when mixed with the electrolyte, cannot directly contribute to ion conductivity (S / cm), adding it to the positive electrode significantly improves its rate performance, cycle performance, and safety. We believe that component 1, due to its specific chemical composition, can participate in the formation of the CEI (cell-encapsulated electrolyte interphase) on the surface of the positive electrode material, altering its composition to make it more stable and preventing CEI rupture and the resulting battery polarization and thermal runaway. This, in turn, improves the rate performance, cycle performance, and safety of the positive electrode in actual battery operation. Simultaneously, component 2 can inhibit electrolyte decomposition and the formation of insulating components on the surface of the positive electrode material. Therefore, when component 2 and component 1 are used together, they can exert a synergistic effect, constructing a superior CEI that simultaneously and comprehensively improves the battery's electrical and safety performance. Especially when component 1 or a mixture of components 1 and 2 forms a coating on the electrode surface, the coating not only separates the positive and negative electrodes to prevent short circuits within the battery, but also improves lithium-ion conduction in the direction parallel to the positive electrode surface and reduces electrolyte decomposition on the positive electrode surface by improving the CEI of the positive electrode surface layer. This is because the positive electrode surface is the area with the most sufficient contact with the electrolyte, and protecting the positive electrode surface can most effectively and comprehensively improve battery performance. Introducing additives into the positive electrode through surface coating does not change the current mainstream manufacturing processes of positive electrodes, separators, and batteries, and helps to improve the rate performance of the battery. It has the advantages of high stability and low cost, making it suitable for large-scale applications.
[0026] Compared with the prior art, the present invention has the following advantages and outstanding effects: The component 1 or the mixture of component 1 and component 2 in the functional layer of the lithium battery positive electrode surface of this invention exhibits high chemical stability. It can be added to the positive electrode after the positive electrode sheet is prepared via surface coating, without altering the current mainstream manufacturing processes for positive electrode sheets, separators, and batteries. It is compatible with the mainstream manufacturing processes of existing lithium-ion battery positive electrode sheets and does not affect the manufacturing processes of the positive electrode and battery cell. It boasts advantages of high stability and low cost, making it suitable for large-scale applications. In contrast, methods of positive electrode material doping or positive electrode surface coating require changes to existing positive electrode material preparation technologies, making it difficult to simultaneously improve discharge specific capacity and rate performance.
[0027] The component 1 added to the lithium battery positive electrode of this invention differs from conventional solid electrolytes in that it has low lithium-ion conductivity. Existing technologies typically select high lithium-ion conductivity additives to improve battery electrical performance. However, we have discovered that by creatively adding low lithium-ion conductivity particles, such as component 1, to the positive electrode, we can significantly improve the battery's rate performance, cycle performance, and safety by enhancing the CEI (Chemical Equilibrium Intake) on the surface of the positive electrode particles, thus overcoming the biases of existing technologies.
[0028] The mixed component particles of component 1 and component 2 added simultaneously to the lithium battery positive electrode sheet of the present invention can improve the stability of CEI on the surface of the positive electrode particles, suppress the release of oxygen from the positive electrode and its reaction with the electrolyte during thermal runaway, and suppress electrolyte decomposition, thereby improving the electrical performance and safety performance of the battery; experiments have shown that the effect is better when component 1 and component 2 are used simultaneously due to synergistic effect.
[0029] Component 1, or a mixture of Component 1 and Component 2, forms a safety coating on the surface of the positive electrode, which can isolate the positive and negative electrodes and improve battery safety. Experiments have shown that batteries with this safety coating do not catch fire or explode during hot-box testing because the safety coating can prevent short circuits by isolating the positive and negative electrodes. The safety coating not only isolates the positive and negative electrodes to prevent internal short circuits, but also improves lithium-ion conduction in the direction parallel to the positive electrode surface and reduces electrolyte decomposition on the positive electrode surface by improving the CEI (Chemical Electrolyte Intake) of the positive electrode surface layer. This is because the positive electrode surface is the area with the most sufficient contact with the electrolyte; protecting the positive electrode surface is the most effective way to improve battery performance.
[0030] The porosity of the functional layer on the lithium battery positive electrode sheet of the present invention is specially designed. If the porosity is less than 20%, it is not conducive to the rate performance of the battery. If the porosity is greater than 80%, it is not conducive to the cycle performance of the battery. The thickness of the functional layer is also specially designed. If the coating thickness is greater than 10 μm, it is not conducive to the rate performance of the battery.
[0031] The positive electrode exhibits excellent rate performance, cycle performance, and safety. Attached Figure Description
[0032] Figure 1 This is a schematic diagram of the structure of the lithium battery positive electrode sheet in Example 1; Figure 2 This is a schematic diagram of the structure of the lithium battery positive electrode sheet in Example 2; Figure 3 This is a schematic diagram of the impact testing fixture of the present invention; Figure 4 Schematic diagram of the lithium battery positive electrode in Example 9 Detailed Implementation The present invention will now be described in detail with reference to the accompanying drawings and embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.
[0033] Example 1 Step 1: Prepare the NCM positive electrode active layer, with an active material mass of 100g; Step 2: Mix 25 kg of component 1 LiTiOPO4 and component 2 Li1.4 Al 0.4 Ti 1.6 The mixed components consisting of (PO4)3 were mixed with 500 kg of NMP and ground into a slurry with a D50 of 300 nm; the ratio of component 1 to component 2 was 1:4.
[0034] Step 3: Add 1 kg of PVDF to the slurry obtained in Step 2 and stir evenly to prepare a coating slurry with a viscosity of 200 mPa·s; Step 4: Coat the slurry obtained in Step 3 onto the NCM90 positive electrode active layer, and dry it to obtain the positive electrode sheet with a coating thickness of 1μm and a porosity of 40%.
[0035] The schematic diagram of the positive electrode sheet for lithium batteries prepared by the above method is shown below. Figure 1 As shown, the electrode includes a current collector 5, a positive electrode material layer on the current collector 5, and a functional layer 3 directly on the positive electrode material layer. The positive electrode material layer includes a positive electrode active material 4, a conductive agent, and a binder. The functional layer 3 includes component 1 particles 1 and component 2 particles 2. The component 1 particles and component 2 particles in the functional layer 3 are uniformly distributed, and some component 1 particles and component 2 particles diffuse into the positive electrode material layer and are distributed between the particles of the positive electrode active material 4. A soft-pack lithium battery is assembled using this positive electrode sheet and matched with a SiOC650 negative electrode. After the prepared lithium battery undergoes liquid injection, formation, and capacity testing, electrochemical and safety performance tests are performed. Specific electrochemical performance test results are shown in Table 1, and safety performance test results are shown in Table 2.
[0036] The lithium battery electrochemical performance testing methods used in this application are as follows: 1. Cyclic performance testing a) Charge at a constant current of 1 C at 23 ℃±2℃ until the charging termination voltage is reached, then switch to constant voltage charging until the charging current rate drops to 0.05 C, stop charging, and let stand for 1 h. b) The battery is discharged at a constant current of 1 C until the discharge termination voltage is reached, then the discharge is stopped and the discharge capacity is recorded; this completes one cycle. c) Repeat steps a and b until the discharge capacity is less than 80% of the discharge capacity in the first cycle, and record the total number of battery cycles at this point.
[0037] 2. Ratio Test a) At 23 ℃±2 ℃, the battery was charged to the charging termination voltage at rates of 0.1 C, 0.2 C, 0.33 C, 1 C, 2 C, and 3 C, respectively, and then discharged to the discharge termination voltage at the same rate. Each cycle was repeated 4 times at the same rate. b) Record the discharge capacity at different discharge rates; c) Calculate the ratio of 2C or 3C discharge capacity to 0.33C discharge capacity, denoted as 2C / 0.33C or 3C / 0.33C, to evaluate rate performance.
[0038] 3. High-temperature cycling a) Charge at a constant current of 1 C at 45 °C until the charging termination voltage is reached, then switch to constant voltage charging until the charging current rate drops to 0.05 C, then stop charging; b) Let the battery stand at 45 ℃ for 5 h; c) Under high temperature of 45 ℃, the battery is discharged at a constant current of 1 C until the discharge termination voltage is reached, then the discharge is stopped and the discharge capacity is recorded; this completes one cycle. d) Repeat steps a to c until the discharge capacity is less than 80% of the discharge capacity of the first cycle. Record the discharge capacity of the battery and the total number of cycles at this point.
[0039] Lithium-ion battery safety performance testing methods: 1. Overcharge a) Charge at a constant current of 1 C at 23 ℃±2℃ until the charging termination voltage is reached, then switch to constant voltage charging until the charging current rate drops to 0.05 C, stop charging, and let stand for 1 h. b) Charge the battery at a constant current of 1 C until thermal runaway occurs, and record the battery voltage value when thermal runaway begins.
[0040] 2. Hot box a) Charge at a constant current of 1 C at 23 ℃±2℃ until the charging termination voltage is reached, then switch to constant voltage charging until the charging current rate drops to 0.05 C, stop charging, and let stand for 1 h. b) Place the battery in the test chamber. The test chamber is heated at a rate of 5 °C / min, and the temperature is maintained at 160 °C ± 2 °C for 1 hour. The battery passes if it does not smoke, catch fire, or explode; otherwise, it fails.
[0041] 3. Fall a) Charge at a constant current of 1 C at 23 ℃±2℃ until the charging termination voltage is reached, then switch to constant voltage charging until the charging current rate drops to 0.05 C, stop charging, and let stand for 1 h. b) The object is dropped freely from a height of 1m onto a concrete slab; Each side of the pouch battery was dropped once, for a total of six tests. After six tests, the battery is considered to have passed if it does not smoke, catch fire, or explode; otherwise, it is considered to have failed.
[0042] 4. Impact of heavy objects a) Charge at a constant current of 1 C at 23 ℃±2℃ until the charging termination voltage is reached, then switch to constant voltage charging until the charging current rate drops to 0.05 C, stop charging, and let stand for 1 h. b) Place battery 8 on the platform surface, and place a metal rod 9 with a diameter of 15.8 mm ± 0.2 mm horizontally on the upper surface of the battery's geometric center. Use a weight of 9.1 kg ± 0.1 kg to freely drop from a height of 610 mm ± 25 mm onto the surface of the battery with the metal rod placed on it, and observe for 6 hours. A schematic diagram of the weight impact test fixture is shown below. Figure 3 10 is the traction rope, 6 is the guide tube, and 7 is the steel impact box (the hinge door is not shown).
[0043] The soft-pack battery is required to undergo impact testing only on its wide side, and each sample must undergo only one impact test. The battery passes if it does not smoke, catch fire, or explode; otherwise, it fails.
[0044] 5. Acupuncture a) Charge at a constant current of 1 C at 23 ℃±2℃ until the charging termination voltage is reached, then switch to constant voltage charging until the charging current rate drops to 0.05 C, stop charging, and let stand for 1 h. b) Using a φ8mm high-temperature resistant steel needle (with a cone angle of 45° at the needle tip, and a smooth surface free of rust, oxide layer and oil), insert the needle at a speed of 25 mm / s from a direction perpendicular to the battery plate, with the insertion point being the geometric center of the pierced surface, and the steel needle remaining in the battery. c) Observe for 1 hour; The battery passes if it does not smoke, catch fire, or explode; otherwise, it fails.
[0045] Example 2 The mixed component consisting of 25 kg of component 1 and component 2 was replaced with only 25 kg of component 1, excluding component 2. The positive electrode active material was replaced with NCM83, and the battery structure was NCM83||SiOC650. Other parameters were the same as in Example 1. The schematic diagram of the prepared lithium battery positive electrode structure is shown below. Figure 2 As shown, the electrode includes a current collector 5, a positive electrode material layer on the current collector 5, and a functional layer 3 directly on the positive electrode material layer. The positive electrode material layer includes a positive electrode active material 4, a conductive agent, and a binder. The functional layer 3 includes component 1 particles 1, wherein the component 1 particles in the functional layer 3 are uniformly distributed, and some component 1 particles diffuse into the positive electrode material layer and are distributed between the particles of the positive electrode active material 4. The lithium battery prepared above was subjected to electrochemical and safety performance tests after liquid injection, formation, and capacity testing. The specific electrochemical performance test results of the lithium battery prepared using this positive electrode are shown in Table 1, and the safety performance test results are shown in Table 2.
[0046] Example 3 Component 2 was replaced with AlPO4, the positive electrode active material was replaced with NCM83, and the negative electrode was replaced with SiOC450. The battery structure was NCM83||SiOC450, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0047] Example 4 Component 2 is replaced with Li 1.4 Al 0.4 Ti 1.6 (PO4)3 and AlPO4, Li in components 1 and 2 1.4 Al 0.4 Ti 1.6 The mass ratio of (PO4)3 to AlPO4 was 1:8:1. The positive electrode active material was replaced with LCO, and the negative electrode with SiOC450. The battery structure was LCO||SiOC450, and other parameters were the same as in Example 1. The prepared lithium battery underwent electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0048] Example 5 The 25 kg mixture of components 1 and 2 was replaced with a mixture containing only 25 kg of component 1, LiTaOSiO4, excluding component 2. The positive electrode active material was replaced with LFP, and the negative electrode was replaced with graphite. The battery structure was LFP||graphite, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0049] Example 6 Component 1 was replaced with LiTaOGeO4, and component 2 was replaced with Li 1.4 Al 0.4 Ge 1.6 (PO4)3 was used, with the positive electrode active material replaced by NCM83 and the negative electrode replaced by graphite. The battery structure was NCM83||graphite, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0050] Example 7 Component 2 is replaced with Li1.4 Al 0.4 Ti 1.6 (PO4)3 and AlPO4, Li in components 1 and 2 1.4 Al 0.4 Ti 1.6 The mass ratio of (PO4)3 to AlPO4 was 1:8:1, and the porosity was replaced with 80%. Other parameters were the same as in Example 1. The lithium battery prepared above was subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0051] Example 8 Component 2 is replaced with Li 1.4 Al 0.4 Ti 1.6 (PO4)3 and AlPO4, Li in components 1 and 2 1.4 Al 0.4 Ti 1.6 The mass ratio of (PO4)3 to AlPO4 was 1:8:1, the porosity was replaced with 20%, and other parameters were the same as in Example 1. The prepared lithium batteries were subjected to electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium batteries are shown in Table 1, and the safety performance test results are shown in Table 2.
[0052] Example 9 Component 2 is replaced with Li 1.4 Al 0.4 Ti 1.6 (PO4)3 and AlPO4, Li in components 1 and 2 1.4 Al 0.4 Ti 1.6 The mass ratio of (PO4)3 to AlPO4 is 1:8:1, the coating thickness is replaced with 500 nm, each primary particle of the mixed component contains particles of both the first and second component crystal forms, the particle size D50 of the primary particles of the mixed component is 300 nm, and the mixed component form of component 1 and component 2 is as follows. Figure 4 As shown, 11 is a mixture of components 1 and 2 in one particle, 3 is the functional layer, 4 is the positive electrode active material, and 5 is the current collector. Other parameters are the same as in Example 1. After the prepared lithium battery is subjected to liquid injection, formation, and capacity testing, electrochemical and safety performance tests are performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0053] Example 10 Component 2 is replaced with Li 1.4 Al 0.4 Ti1.6 (PO4)3 and AlPO4, Li in components 1 and 2 1.4 Al 0.4 Ti 1.6 The mass ratio of (PO4)3 to AlPO4 was 1:8:1, and the coating thickness was replaced with 10 μm. Other parameters were the same as in Example 1. The lithium battery prepared above was subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0054] Example 11 Component 2 is replaced with Li 1.4 Al 0.4 Ti 1.6 (PO4)3 and AlPO4, Li in components 1 and 2 1.4 Al 0.4 Ti 1.6 The mass ratio of (PO4)3 to AlPO4 was 1:8:1, the porosity was replaced with 20%, and the D50 of the mixed component consisting of components 1 and 2 was 50 nm. Other parameters were the same as in Example 9. The lithium battery prepared above was subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0055] Example 12 Component 2 is replaced with Li 1.4 Al 0.4 Ti 1.6 (PO4)3 and AlPO4, Li in components 1 and 2 1.4 Al 0.4 Ti 1.6 The mass ratio of (PO4)3 to AlPO4 was 1:8:1. The D50 of the mixed component consisting of components 1 and 2 was replaced with 1 μm, and other parameters were the same as in Example 9. The lithium battery prepared above was subjected to electrochemical and safety performance tests after liquid injection, formation, and capacity testing. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0056] Example 13 Component 2 is replaced with Li 1.4 Al 0.4 Ti 1.6 (PO4)3 and AlPO4, Li in components 1 and 2 1.4 Al 0.4 Ti 1.6The mass ratio of (PO4)3 to AlPO4 is 1:8:1. The D50 of the mixed component consisting of components 1 and 2 is replaced with 50 nm, and the coating thickness is replaced with 10 nm. Other parameters are the same as in Example 9. After the prepared lithium battery is subjected to liquid injection, formation, and capacity testing, electrochemical and safety performance tests are performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0057] Comparative Example 1 Component-free 1 and Component-free 2, with other parameters the same as in Example 1; the lithium batteries prepared above were subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium batteries are shown in Table 1, and the safety performance test results are shown in Table 2.
[0058] Comparative Example 2 Component 1 and Component 2 were used, with the positive electrode active material replaced by NCM83. The battery structure was NCM83||SiOC650, and other parameters were the same as in Example 1. The prepared lithium batteries were subjected to electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium batteries are shown in Table 1, and the safety performance test results are shown in Table 2.
[0059] Comparative Example 3 Component 1 and Component 2 were omitted, with the positive electrode active material replaced by NCM83 and the negative electrode by SiOC450. The battery structure was NCM83||SiOC450, and other parameters were the same as in Example 1. The prepared lithium batteries were subjected to electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium batteries are shown in Table 1, and the safety performance test results are shown in Table 2.
[0060] Comparative Example 4 Component 1 and Component 2 were omitted, with the positive electrode active material replaced by LCO and the negative electrode being SiOC450. The battery structure was LCO||SiOC450, and other parameters were the same as in Example 1. The prepared lithium batteries were subjected to electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium batteries are shown in Table 1, and the safety performance test results are shown in Table 2.
[0061] Comparative Example 5 Component 1 and Component 2 were omitted, with the positive electrode active material replaced by LFP and the negative electrode being graphite. The battery structure was LFP||graphite, and other parameters were the same as in Example 1. The prepared lithium batteries were subjected to electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium batteries are shown in Table 1, and the safety performance test results are shown in Table 2.
[0062] Comparative Example 6 Component 1 and Component 2 were omitted, the positive electrode active material was replaced with NCM83, the negative electrode was graphite, and the battery structure was NCM83||graphite. Other parameters were the same as in Example 1. The lithium batteries prepared above were subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium batteries are shown in Table 1, and the safety performance test results are shown in Table 2.
[0063] Comparative Example 7 The 25 kg mixture of components 1 and 2 was replaced with 25 kg of Al2O3, with other parameters remaining the same as in Example 1. The prepared lithium battery underwent electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0064] Comparative Example 8 The 25 kg mixture of components 1 and 2 was replaced with 25 kg of ZnO, and the positive electrode active material was replaced with NCM83. The battery structure was NCM83||SiOC650, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0065] Comparative Example 9 Replace 25 kg of the mixed component consisting of component 1 and component 2 with 25 kg of Li. 1.4 Al 0.4 Ti 1.6 The positive electrode active material was replaced with NCM83, and the negative electrode was replaced with SiOC450. The battery structure was NCM83||SiOC450, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0066] Comparative Example 10 The 25 kg mixture of components 1 and 2 was replaced with 25 kg of AlPO4, the positive electrode active material was replaced with LCO, and the negative electrode was replaced with SiOC450. The battery structure was LCO||SiOC450, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0067] Comparative Example 11 Replace 25 kg of the mixed component consisting of component 1 and component 2 with 25 kg of Li. 0.5 La 0.5 TiO3 was used, with the positive electrode active material replaced by LFP and the negative electrode replaced by graphite. The battery structure was LFP||graphite, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0068] Comparative Example 12 Replace 25 kg of the mixed component consisting of component 1 and component 2 with 25 kg of Li7La3Zr2O. 12 The positive electrode active material was replaced with NCM83, and the negative electrode was replaced with graphite. The battery structure was NCM83||graphite, and other parameters were the same as in Example 1. After the prepared lithium battery underwent liquid injection, formation, and capacity testing, electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0069] Table 1 shows the electrochemical performance data of the examples.
[0070] Table 1
[0071] Table 2 shows the safety performance data of the embodiments.
[0072] Table 2
[0073] As shown in Tables 1 and 2, coating the positive electrode surface with a functional layer containing component 1 or a mixture of component 1 and component 2 can significantly improve the rate performance, cycle performance, and safety performance of the battery. A comparison between Example 5 and Comparative Example 11 shows that coating the positive electrode with component 1 is far more effective in improving the rate performance, cycle performance, and safety performance than coating the positive electrode with a high lithium-ion conductivity solid electrolyte. This is because constructing an efficient CEI is key to improving the electrical and safety performance of both liquid and solid-state batteries. A comparison between Example 1 and Examples 7 and 8 shows that the porosity of the functional layer on the lithium battery positive electrode sheet of the present invention has an optimal design. If the porosity is too small, it is detrimental to the battery's rate performance; if the porosity is too large, it is detrimental to the battery's cycle performance. A comparison between Example 1 and Examples 9, 10, and 13 shows that the functional layer has an optimal thickness. Too small a thickness is detrimental to safety performance, while too large a thickness is detrimental to rate performance. By comparing Example 1 with Examples 11 and 12, it can be seen that Component 1 and Component 2 have optimal particle sizes. Optimizing the particle size can improve the electrical performance and safety performance of the battery. If the particle size is too small, the additive particles are prone to agglomeration, which affects the rate performance. If the particle size is too large, the additive particles cannot fully contact the surface of the active material particles, which especially affects the rate performance and safety performance. Both too small and too large particle sizes are not conducive to the construction of a stable CEI.
[0074] It is understood that the above embodiments are merely exemplary implementations used to illustrate the principles of the present invention, and the present invention is not limited thereto. For those skilled in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.
Claims
1. A lithium battery positive electrode sheet, the positive electrode sheet comprising a positive electrode material layer and a functional layer directly located on the positive electrode material layer, wherein, The functional layer is formed by coating a coating slurry comprising component 1 and component 2 onto a positive electrode material layer and drying it at 80-180°C, characterized in that: The functional layer material includes component 1, which is selected from Li 1-x1 Ti 1-x1 A x1 OPO4, Li 1-x1 Ti 1-x1 A x1 PO5, Li 2- y1 Ti 1-y1 A y1 OM1O4, Li 2-y1 Ti 1-y1 A y1 At least one of M1O5, wherein 0≤x1≤0.7, 0≤y1≤1, A is selected from at least one of Nb, Ta, and Sb, and M1 is selected from at least one of Si and Ge; The functional layer material further includes component 2, which is selected from LiM22(PO4)3, Li 1+x2 Al x2 M2 2-x2 (PO4)3, M2O2, Li 16-4y2 M2 y2 At least one or more combinations of O8, M2P2O7, M3PO4, M32SiO5, M43(PO4)2, and M42SiO4, wherein M2 is selected from Ti, Ge, Zr, and Hf, where 0 < x2 < 0.6, and M3 and M4 are independently selected from any one of Al, Ga, Sc, Y, Ca, Sr, Zn, Si, In, Lu, La, Fe, Cr, and Ge. <y2<4; The components 1 and 2 are uniformly distributed, and some of the components 1 and 2 diffuse into the positive electrode material layer and are distributed among the positive electrode active material particles in the positive electrode material layer; the functional layer is a three-dimensional porous structure with a porosity of p, where 20%≤p≤80%, and a thickness of h, where 0μm<h≤10μm.
2. The lithium battery positive electrode sheet according to claim 1, characterized in that: In the functional layer material, the mixed component form consisting of component 1 and component 2 is either a uniform mixture of component 1 particles and component 2 particles, or each primary particle contains both component 1 crystal form and component 2 crystal form.
3. The lithium battery positive electrode sheet according to claim 1 or 2, characterized in that: Component 1 is selected from LiTiOPO4, Li 0.9 Nb 0.1 Ti 0.9 OPO4, Li 0.9 Ta 0.1 Ti 0.9 At least one of OPO4, Li2TiOSiO4, and LiTaOGeO4; And / or, component 2 is one of InPO4, LATP, AlPO4, LAGP, LATP+AlPO4, LAGP+Al2SiO5, InPO4+LATP, Al2SiO5, TiO2+LiTi2(PO4)3, TiP2O7+LiGe2(PO4)3.
4. The lithium battery positive electrode sheet according to claim 1 or 2, characterized in that: The particle size of component 1 in the functional layer is 10 nm-10 μm.
5. The lithium battery positive electrode sheet according to claim 4, wherein, The particle size of component 1 in the functional layer is 50 nm-1 μm.
6. The lithium battery positive electrode sheet according to claim 1 or 2, characterized in that: The particle size of component 2 in the functional layer is 10 nm-10 μm.
7. The lithium battery positive electrode sheet according to claim 6, wherein, The particle size of component 2 in the functional layer is 50 nm-1 μm.
8. The lithium battery positive electrode sheet according to claim 1 or 2, characterized in that: The positive electrode active material includes at least one of lithium cobalt oxide positive electrode and its modified material, NCM ternary positive electrode and its modified material, NCA ternary positive electrode and its modified material, lithium nickel manganese oxide positive electrode and its modified material, lithium-rich positive electrode and its modified material, and lithium iron phosphate positive electrode and its modified material.
9. A method for preparing a lithium battery positive electrode sheet according to any one of claims 1-8, characterized in that, Includes the following steps: Step 1: Prepare the positive electrode active layer; Step 2: Mix component 1 or a mixture of component 1 and component 2 with the solvent until homogeneous, and grind into a slurry of 10nm-10μm; Step 3: Add binder to the slurry obtained in Step 2 and mix evenly to prepare a coating slurry; Step 4: Coat the slurry obtained in Step 3 onto the positive electrode active layer and dry it to obtain the positive electrode sheet.
10. The preparation method according to claim 9, characterized in that: The solvent includes at least one of deionized water, ethanol, NMP, isopropanol, and acetone.
11. A lithium battery cell, characterized in that: The lithium battery cell includes a positive electrode, a negative electrode, a separator, an electrolyte, and a casing, wherein the positive electrode is the positive electrode as described in any one of claims 1-8.
12. The lithium battery cell according to claim 11, characterized in that: The lithium battery is either a liquid battery or a solid battery.
Citation Information
Patent Citations
A quasi-solid-state electrolyte, its preparation method and application
CN108365260B
A lithium-ion battery separator and its preparation method
CN108963153B
Strontium-doped ternary lithium ion battery positive electrode material, and preparation method and application thereof
CN113224287A
Phosphite lithium ion battery electrolyte additive and application thereof
CN113690490A
Positive pole piece containing solid electrolyte, and preparation method and application thereof
CN113707880A